Financial Development and Energy Consumption: Evidence from Germany - Denisova, Valeriia (International Journal of Energy Economics and Policy, 2020)
This paper investigates the influence of several variables of financial development on electricity consumption in case of Germany. We assume that financial market development, economic growth and urbanization lead to an increase in energy consumption. The hypothesis is tested on example of Germany for the period 1990–2018. The results partly confirm the hypothesis. We found that economic growth and urbanization positively affect the energy consumption, while financial market development does not show statistical significance. Keywords: Financial Market, Energy Consumption, Urbanization, Economic Growth JEL Classifications: D53, Q41, P25, O47 DOI: https://doi.org/10.32479/ijeep.8603